1976
DOI: 10.1111/j.1095-8339.1976.tb01356.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Hordeum murinum aggregate: 1. Morphology

Abstract: Morphological data has been assembled from a large collection of fruiting heads of the Hordeum murinum aggregate. Computer analysis reveals two major taxa, which, using seven characters, can be readily separated. These are recognized as H. murinum L. and H. leporinum Link. The former is primarily north‐western and the latter south‐eastern in distribution. Both plants can occur sympatrically, and there is no evidence of a cline. Diploid plants from south‐east Europe represent extreme H. leporinum types and thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…leporinum and subsp. murinum (Booth and Richards 1976, 1978; Richards and Booth 1977; Giles and Lefkovitch 1986). It has been introduced as a weed to most parts of the world, especially subsp.…”
Section: Introductionmentioning
confidence: 99%
“…leporinum and subsp. murinum (Booth and Richards 1976, 1978; Richards and Booth 1977; Giles and Lefkovitch 1986). It has been introduced as a weed to most parts of the world, especially subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Booth & Richards (1976& Richards ( , 1978 and Richards & Booth (1977) found a more complicated pattern based on elaborate studies of karyotype variation, protein electrophoresis and morphological variation (treated numerically). They suggested a morphologically based taxonomy where leporinum and glaucum should be treated within the same species, and murinum, as a discrete one.…”
Section: Historical Outlinementioning
confidence: 99%
“…Numerous chromosome counts have shown that it is tetraploid throughout its range (cf. Fedorov 1969, Queiros 1973, Dahlgren et al 1974, Loon 1974, except from Turkey, Armenia, Iran and Pakistan to Afghanistan and Kazakhstan where it also is hexaploid and mixed with the tetraploid cytotype (Bowden 1962, Booth & Richards 1976, 1978.…”
Section: Taxonomymentioning
confidence: 99%
“…Booth and Richards (1976) treat H . Jaaska carried out electrophoretic isozyme analysis and found that "H. geniculatutn is distinctly different from H. marinurn s. str.…”
Section: ( a ) Three Ttrxn: [ I ] H Marirz~rtn (Scr~slr Lato) [2] mentioning
confidence: 99%